Analisis media Gambar dalam Kitab Nahwu Silsilah Ta’lim al-Lughah al-‘Arabiyah Mustawa Tsalits: Analysis of Visual Media in the Book Nahwu Silsilah Ta'lim al-Lughah al-'Arabiyah Mustawa Tsalits - Wandi; M.Faisol; Idrus Muchin bin Agil (Universitas Negeri Semarang, 2025)
Arabic is a key language in understanding the teachings of Islam, including the Qur’an and the Sunnah. One of the essential branches in learning Arabic is nahwu (Arabic grammar), which serves as a foundation for understanding other Islamic sciences. Nahwu Mustawa Three, part of the Silsilah Ta’lim al-Lughah al-‘Arabiyah series compiled by experts at Jami’ah al-Imam Muhammad ibn Suud al-Islamiyah, is a grammar textbook designed for non-native Arabic speakers and has been widely used globally, including in Indonesia. this study aims to analyze the use of visual media in the textbook, considering that visual aids play a significant role in enhancing student interest and comprehension. The research method used is descriptive qualitative, with data analyzed using Krippendorff’s content analysis technique. the primary data source is the content of Nahwu Mustawa Three, while secondary data were obtained from supporting literature such as books and journals.the results show that the textbook utilizes two types of images: thematic images and semantic images. Thematic images function as contextual or thematic illustrations of the lesson, while semantic images are used to visually introduce vocabulary. Mnemonic images were not found in the textbook. Nevertheless, the two types of images used have proven effective in supporting learning and increasing student motivation. Therefore, the use of visual media in Nahwu Mustawa Tsalits is considered appropriate and effective as a learning aid in teaching Arabic grammar.